LEONIDAS N. YEROVI Y LA MODERNIDAD CRIOLLA EN LA REPÚBLICA ARISTOCRÁTICA (1895-1919) - Velasquez Castro, Marcel (2005)
This article analyzes the political poetry and the journalistic articles ofLeonidas N. Yerovi as vehicles for the a formalization and setting up ofthe modernity processes in the cultural sphere ofthe República Aristocrática.Yerovi, founder of Peruvian modern journalism, expresses aCreole modernity that confronts the modernization imposed by PartidoCivil s elites. His texts remain ambivalent about mass culture andemergent social movements. His critical view on everyday life, socialpractices and the political sphere of Lima transformed the Creo le culturaltradition decisively.